Pendidikan Agama Islam di Era Digital Berbasis Holistik-Integratif - Ajusman, Ajusman; Asman (RELIGI: Jurnal Pendidikan Agama Islam, 2024)
The Islamic religious education material taught in schools currently still stands on its own, both in terms of its scientific field and in terms of other scientific aspects. Islamic religious education in the digital era must be based on an integrative holistic approach, this is due to the anxiety in education regarding the character of the students. is a scourge in education today, as well as the challenges of a very rapid era. The aim of this research is to find out Islamic religious education in the digital era based on an integrative holistic approach. The method used is library research (Library Research) by collecting and analyzing books and articles related to the theme. The results of this research: Integrative holistic Islamic religious education is an educational approach that aims to form complete students, not only from a cognitive perspective, but also morally and spiritually. This approach is expected to be able to answer current educational problems, namely moral degradation. Integrative holistic Islamic religious education is an educational approach that integrates religious knowledge with digital technology knowledge. This approach is expected to produce students who have adequate knowledge and skills, and have noble character.